TAX PREFERENCES IN THE CZECH AND POLISH PERSONAL INCOME TAXES - Burzec, Marcin (Review of European and Comparative Law, 2017)
Article presents tax preferences in Czech Republic and Poland in the comparative aproach. The aim of the comparative study is to show how particular problems can be tackled by different countries by different measures. Both in Poland and the Czech Republic it is possible to identify common problems in the area of the tax law. One of such problems is an appropriate shape of tax preferences within the income tax contruction. The aim of the present article is to demonstrate how Poland and the Czech Republic, by shaping tax preferences within the construction of the income tax, tackle the problem of the taxpayer’s ability to pay. Further, it is shown how the two countries, by means of tax instruments, supplement their policy in areas as important as pro-family policy, supporting subjects implementing public tasks, the pension system, policy on people with disabilities, and housing policy.